Alkali Carbonate Molten Salt Coated Calcium Oxide with Highly Improved Carbon Dioxide Capture Capacity. Issue 8 (21st March 2017) - Huang, Liang; Zhang, Yu; Gao, Wanlin; Harada, Takuya; Qin, Qingqing; Zheng, Qianwen; Hatton, T. Alan; Wang, Qiang
Abstract: CO2 reduction is crucial if the effects of this gas on global warming are to be alleviated. We report for the first time an alkali carbonate molten salt promoted CaO‐based CO2 sorbent with CO2 capture performance superior to that of neat CaO. The influences of chemical composition, loading, and melting temperature of the (Li–Na–K)2 CO3 molten salts and of the calcination and adsorption temperatures on CO2 capture were evaluated systematically. The microstructural and morphological evolution of the samples during CO2 adsorption was studied by X‐ray diffraction, scanning electron microscopy, and Fourier‐transform infrared spectroscopy analyses. The (Li–K)2 CO3 molten salt coating was found not only to promote CO2 uptake but also to facilitate CO2 desorption from CaO. In particular, at low temperatures of 500 and 600 °C, the CO2 capture capacity increased significantly from 1.19 and 3.26 mmol g −1 to 6.93 and 10.38 mmol g −1, respectively. The melting point of the molten salts was also a crucial factor in the improvement of CO2 uptake. Kinetic studies based on fractal‐like models indicated that the rate coefficients for (Li–K)2 CO3 /CaO were approximately 3.3 to 3.8 times larger than those for neat CaO. The coating of alkali carbonate molten salts is believed to prevent the formation of a rigid CaCO3 layer on the surface of the CaO particles and to provide continuous delivery of CO3 2− to promote CO2 capture. During the CO2 adsorption/desorption cycling tests, (Li–K)2 CO3 /CaO resulted in a stable and reversible CO2 uptake of 6.0–6.3 mmol g −1, which is much higher than that of neat CaO (2.0 mmol g −1 ). Abstract : How low can you go : A molten salts promoted CaO sorbent is reported for CO2 capture for the first time and shows markedly improved CO2 capture capacity at 400 to 600 °C (especially at low temperatures). This work represents a novel scheme for preventing the sintering of CaO by shifting its operation temperatures to a lower temperature window.